Cytotoxicity of organic surface coating agents used for nanoparticles synthesis and stability. Issue 4 (June 2015) - Zhang, Ying; Newton, Brandon; Lewis, Eybriunna; Fu, Peter P.; Kafoury, Ramzi; Ray, Paresh C.; Yu, Hongtao
Graphical abstract